Metagenomic shotgun sequencing of blood to identify bacteria and viruses in leukemic febrile neutropenia - Prakhar Vijayvargiya; Adeline Feri; Mathilde Mairey; Cécile Rouillon; Patricio R. Jeraldo; Zerelda Esquer Garrigos; Matthew J. Thoendel; Kerryl E. Greenwood-Quaintance; M. Rizwan Sohail; Priya Sampathkumar; Megan T. Spychalla; A. K. Stewart; et al. (PLoS ONE, 2022)
Despite diagnostic advances in microbiology, the etiology of neutropenic fever remains elusive in most cases. In this study, we evaluated the utility of a metagenomic shotgun sequencing based assay for detection of bacteria and viruses in blood samples of patients with febrile neutropenia. We prospectively enrolled 20 acute leukemia patients and obtained blood from these patients at three time points: 1) anytime from onset of neutropenia until before development of neutropenic fever, 2) within 24 hours of onset of neutropenic fever, 3) 5–7 days after onset of neutropenic fever. Blood samples underwent sample preparation, sequencing and analysis using the iDTECT® Dx Blood v1® platform (PathoQuest, Paris, France). Clinically relevant viruses or bacteria were detected in three cases each by metagenomic shotgun sequencing and blood cultures, albeit with no concordance between the two. Further optimization of sample preparation methods and sequencing platforms is needed before widespread adoption of this technology into clinical practice.